Penatalaksanaan Fisioterapi Untuk Penderita Cerebral Palsy Spastik Diplegi Di Yayasan Sayap Ibu Cabang Yogyakarta - Panulat, Pandu Dwi, Umi Budi Rahayu S.Fis. S.Pd, M.Kes (2015)
Background: Cerebral Palsy is a collection of motor disorders resulting from damage to the brain that occurs before, during or after birth. The damage to the child's brain affects the motor system and as a result the child has poor coordination, poor balance, or abnormal movement patterns or a combination of these characteristics. Diplegia is a form of cerebral palsy primarily affecting the legs. Most children with cerebral palsy have some problems with their upper extremities, but for a child with diplegia, the upper extremities are clearly much less involved than the lower extremities. The problems that arise in this condition is abnormal muscle tone in the form of spasticity, shortening of the muscles or contracture of the lower limb so that the range of motion is reduced and the limitations of functional capabilities such standing and walking. With an alternative form of Snoezelen therapy, massage and passive stretching and play therapy is expected to help the problems that occur in these conditions. Aims of Research: To study about physiotherapy management in the case of spastic cerebral palsy diplegia by using alternative therapies, such as Snoezelen to reduce spasticity through relaxation effects produced, Massage and passive stretching of the muscles of the lower limb shortening and exercise with play therapy approach for gross motor skills and abilities functional activity. Result: After treatment for about six times the obtained results of the assessment of spasticity with asworth scale T1: Hip 1, 3 ankle, knee 3 to T6: Hip 1, 2 ankle, knee 2. Increased passive range of motion in the lower extremity, T1: hip dextra S 10 -0-85, F 35-0-5, Hip sinistra S 10-0-85, F 30-0-5, knee dextra S 0-30-95, knee sinistra S 0-25-100, ankle dextra S 5 -30-35, ankle sinistra S 5-30-35, become T6: hip dextra S 10-0-100, F 40-0-10, Hip sinistra S 10-0-100, F 40-0-10, knee dextra S 0-25-100, knee sinistra S 0-20-105, ankle dextra S 15-20-40, ankle sinistra S 15-20-40. The increase in gross motor skills with the GMFM, T0: Total score of 28.92% to T6: 34.23%. Increased functional activity of the Barthel index, T0: The total score of 70 to T6: 80. Conclusion: Giving Snoezelen able to provide relaxation that affect reduction of spasticity, massage and passive stretching effect on the muscles of the lower limbs that have contractures or muscle shortening,it is marked by an increase in range of motion performed passively. Exercise with approach through play therapy able to increase gross motor skills and abilities of functional activity in patients with spastic cerebral palsy diplegia